2019
DOI: 10.3390/ijerph16081376
|View full text |Cite
|
Sign up to set email alerts
|

Job Crafting as a Mediator between Work Engagement and Wellbeing Outcomes: A Time-Lagged Study

Abstract: This time-lagged study, using the framework of the JD-R model, tested the mediating role of job crafting measuring: at T1, work engagement, workaholism and emotional exhaustion; at T2, job crafting; and, at T3, flourishing, job performance and job satisfaction. Respondents were 443 Spanish employees working in different companies. Results show that job crafting mediates the relationship between work engagement and some of its outcomes (job performance and flourishing). In particular, the job crafting component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 54 publications
2
50
2
1
Order By: Relevance
“…Overall, humor and humor styles can be conceived as a promising primary prevention resource for work and organizational contexts. More generally, humor and humor styles could be considered as a useful new preventive resource to promote employee health and safety, as well as organizational effectiveness and sustainability (i.e., healthy organization) [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, humor and humor styles can be conceived as a promising primary prevention resource for work and organizational contexts. More generally, humor and humor styles could be considered as a useful new preventive resource to promote employee health and safety, as well as organizational effectiveness and sustainability (i.e., healthy organization) [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76].…”
Section: Discussionmentioning
confidence: 99%
“…According to the broaden-and-build theory ( Fredrickson, 2001 ) and JD-R model ( Bakker and Demerouti, 2007 ) and based on existing studies showing significant associations of positive and negative emotions with work engagement ( Sonnentag et al, 2008 ; Malinowski and Lim, 2015 ; Buriæ and Macuka, 2018 ) and psychological well-being ( Lavy and Eshet, 2018 ), we first assumed that positive emotions and the positivity ratio will be positively associated with teachers’ work engagement and psychological well-being. Second, considering the positive associations of work engagement with well-being and flourishing ( Robledo et al, 2019 ; Tesi et al, 2019 ), we predicted that teachers’ work engagement will be positively related to psychological well-being. Third, as our main hypothesis, we predicted that teachers’ work engagement will mediate the association of emotions and positivity ratio with psychological well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Most uncertain was the role of task crafting, only stimulating positive responses in conjunction with other forms of control. In this regard, this study deviates from current research that has confirmed the positive effects of job crafting, and using advanced methods, such as diary, multi-level and longitudinal study designs [22][23][24]. This study differs from these investigations by also including task autonomy and idiosyncratic deals, thus separating (i.e., statistically "partializing out") the effects of these three types of task control, which otherwise may be confounded in the measurement of job crafting.…”
Section: Discussionmentioning
confidence: 63%